Cutaneous Metastasis of Medullary Carcinoma Thyroid Masquerading as Subcutaneous Nodules Anterior Chest and Mandibular Region - Rahul Mannan; Jasmine Kaur; Jasleen Kaur; Sanjay Piplani; Harjot Kaur; Harleen Kaur (Case Reports in Dermatological Medicine)
Cutaneous metastasis of underlying primary malignancies can present to dermatologist with chief complaints of cutaneous lesions. The underlying malignancy is generally diagnosed much later after a complete assessment of the concerned case. Medullary carcinoma thyroid (MCT) is a relatively uncommon primary neoplasia of the thyroid. Very few cases presenting as cutaneous metastases of MCT have been reported in the literature. Most of the cases which have been reported are of the papillary and the follicular types. We here report a case of a patient who presented in the dermatology clinic with the primary complaint of multiple subcutaneous nodules in anterior chest wall and left side of body of mandible. By systematic application of clinical and diagnostic skills these nodules were diagnosed as cutaneous metastasis of MCT bringing to the forefront a history of previously operated thyroid neoplasm. So clinically, the investigation of a flesh coloured subcutaneous nodule, presenting with a short duration, particularly in scalp, jaw, or anterior chest wall should include possibility of metastastic deposits. A dermatologist should keep a possibility of an internal organ malignancy in patients while investigating a case of flesh coloured subcutaneous nodules, presenting with short duration. A systematic application of clinical and diagnostic skills will eventually lead to such a diagnosis even when not suspected clinically at its primary presentation. A prompt and an emphatic diagnosis and treatment will have its bearing on the eventual outcome in all these patients.